Potential antibacterial compounds from Malaysian Sponges Neopetrosiaexigua - Qaralleh, Haitham; Syed Osman Idid, Syed Zahir Idid; Saad, Shahbudin; Darnis, Deny Susanti; Bakhtiar, M. Taher (2010)
This study was carried out to isolate the active antibacterial compounds from marine sponge Neopetrosiaexigua. Using disc diffusion method, methanol extract of N. exigua showed a significantantibacterial activity. Sequentially, liquid-liquid extraction was performed using different polarity solvents ( n-hexane, carbon tetrachloride, dichloromethane, n-butanol and water) in order to isolate the active antibacterial compounds. Based on the biological guided fractionation results, diccholoromethane and n-butanol fractions showed the higher antimicrobial activity than other solvents. Purification of n-butanol fraction was done by using Sephadex LH-20, normal phase column chromatography (eluted with water/acetonitrile and acetonitrile/methanol) to yeild four compounds (1-4). All compounds weretested for their antibacterial activity against Bacillus anthracis. The results showed that oth compond 3 and 4 exhibited a significant antibacterial activity. Although the spectroscopy (NMR and FTIR) analysiswas performed, research is still in progress to elucidate the structures of the isolated compounds.